Evaluation of a Restoration Approach After One Century – Effects of Admixed European Beech on the Natural Regeneration Potential and Humus Condition in Spruce Stands - Axer, Maximilian; Kluckow, Fabian; Wagner, Sven (Frontiers in Forests and Global Change, 2022)
About 100 years ago, groups of European beech were reintroduced into Norway spruce stands in some parts of Germany as a restoration approach. The aim of this approach was to maintain or rehabilitate the ecological function of soil fertility and the regeneration option of beech for the next generation. The effect of beech groups on surrounding spruce stands was studied in the Ore Mountains by recording natural regeneration of beech and humus layer thickness and form. Point pattern statistics were used to analyse the spread of beech regeneration and to determine factors influencing its establishment. It was found that the density of regeneration decreases with increasing distance from the beech group. However, beech regeneration was found up to distances of 69 m. Furthermore, it becomes evident that PAR radiation (maximum regeneration densities at PAR values of 35 W/m²) and fencing (3.41 times higher regeneration density compared to unfenced areas) against deer have a positive influence on beech regeneration density. Ordered categorical models were used to model humus form and non-linear models were used to model humus layer thickness. It could be proven that the most bioactive humus forms and lowest humus layer thicknesses were found within the beech group. With increasing distance to the beech group, the total humus layer thickness and the proportion of mormoder in the spruce stand increased. The positive influence of the beech group on the humus composition extends to about 40 m from the centre of the beech group. Due to the former arrangement of the beech groups in the terrain, the effects can also extend to the spruce stands in between. The hypotheses on the restoration approach of reintroducing groups of beech into spruce stands formulated by foresters 100 years ago can thus be confirmed. For future restoration approaches of spruce stands, groupwise mixtures of beech should be established with a distance of 40-50 m.